Racismo ambiental e violência identitária: um estudo sociológico dos impactos socioambientais de projetos de barragens no estado do Mato Grosso - Poquiviqui, Agilson (2019)
This thesis aims to understand the social and identity impacts in the life of the affected caused by the probable establishment of the dam of the Castanheira Hydroelectric Power Plant, located in the city of Juara, Mato Grosso. The realization of this venture in the region can, directly or indirectly, reach indigenous, riverside and fishermen ethnic groups of the Arinos Valley region, in so far as it promotes not only environmental inequalities, characteristics of this type of mega water investment, but above all by inducing society to new modalities of environmental racism towards the social agents of the flooded area. Power generation policies based on water resources have met capitalist interests, as well as the market, which has become increasingly aggressive, thus disregarding the position of social agents, alienating them from their rights and confronting their freedoms. The approach to the problem in question is via qualitative social research. More specifically, the social and environmental problems that transform the relationships of these social agents will be approached from the beginning of the case studies, focusing on life stories. For data generation were used documentary research and semi-structured interviews, as well as photocumentation and field notebook. The consequences of the construction of the HPP consists, to a certain extent, in the denial of rights and disrespect for the freedom of those affected, especially in relation to the different ways of being and being in the world, ie, there is no respect for identities and memories. For it is perceived apparent disregard for the material and immaterial goods of these peoples. Such evidence is a form of environmental racism, which occurs from the planning stage, and even before the project obtains a land occupation license, the life expectancies of those affected are already affected.